Transformasi Sosial Masyarakat Akibat Implementasi Gerakan Nasional Non Tunai (GNNT) dalam Sektor Ekonomi dan Keuangan Negara - Irwan Triadi; Dimas Yanuarsyah (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2025)
The use of non-cash payments is increasingly becoming a trend among Indonesians, both in urban and rural areas. Non-cash payment instruments are considered more effective in supporting transaction activities and contribute significantly as the main driver of national economic growth. The state, as the organizer of public welfare, is obliged to carry out various activities to achieve the welfare of the people, as mandated in the Preamble of the 1945 Constitution of the Republic of Indonesia. In the beginning, money as a medium of exchange was in concrete form such as coins and banknotes. However, rapid technological developments encourage the birth of innovation in payment systems through electronic methods, to support the optimization of the use of non-cash payment instruments (less cash), so that a society with digital-based financial transactions is formed (less cash society). This research uses a normative juridical approach, relying on secondary data obtained from primary legal materials, secondary legal materials, and tertiary legal materials. The main focus of this research is to analyze the influence of the National Non-Cash Movement (GNNT) on social changes in the economic field. Based on the provisions of Article 1 point 3 of Bank Indonesia Regulation Number 16/8/PBI/2014 concerning Amendments to Bank Indonesia Regulation Number 11/12/PBI/2009 concerning Electronic Money, it is stated that electronic money is a payment instrument that fulfills a number of certain elements related to its use.